First-principles study of direct CO₂ dissociation on Ni-decorated graphene - Bautista, Reilly V. (Animo Repository, 2024)
One way to mitigate the effects of the anthropogenic climate change is to significantly reduce the level of greenhouse gases in the atmosphere such as CO₂. The relatively high dissociation energy of CO₂ poses a major challenge in designing an industrial process to break it down. In this study, the feasibility of using single-atom Ni-decorated graphene as a catalyst for the direct CO₂ dissociation process (defined in two steps: (1) CO₂ → CO + O and (2) CO → C + O) was determined through a combination of density functional theory and climbing image nudged elastic band method. It is found out that the Ni-decorated graphene significantly reduced the associated dissociation energy for each step. While not exhaustive, this study opens a new avenue for investigating the feasibility of CO₂ dissociation as a viable industrial process and also the use of graphene as a support structure in industrial processes.